IMPLEMENTASI PASAL 12 UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 21 TAHUN 2007 TENTANG PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG DALAM MEMBERANTAS TINDAK PIDANA PROSTITUSI DI WILAYAH HUKUM KEPOLISIAN RESOR KAMPAR - Muhammad Adil. MA; Mukhlis R; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One form of human trafficking is prostitution. Prostitution in Indonesia is considered acrime against decency and is illegal and against human rights. One way to eradicateprostitution is to punish users of their services, by making Commercial Sex Workers (PSK)victims of sexual exploitation in trafficking in persons, through Article 12 of the Law of theRepublic of Indonesia Number 21 of 2007 concerning the Eradication of Trafficking inPersons.This type of research can be classified as sociological juridical research. With theresearch location taking place in Kampar Regency, especially in the Kampar Resort PoliceLegal Area. While the population and sample are all parties related to the problem beingstudied. This study uses data sources in the form of primary data and secondary data, anddata collection techniques are carried out by means of interviews.The results of the study concluded that, First, the implementation of Article 12 of thePTPPO Law has never been applied to users of prostitution services who sexually exploit sexworkers who are victims of trafficking in persons in the Judicial Area of the Kampar ResortPolice; Second, the main factor hindering the implementation of Article 12 of the PTPPOLaw in eradicating criminal acts of prostitution in the Kampar Resort Police Legal Area, isdue to the lack of commitment from the government, community and law enforcement officialsto fight together in eradicating criminal acts of prostitution in trafficking in persons, thenservice users. prostitution often uses fake identities, and victims are reluctant to providecomplete information to uncover prostitution networks in human trafficking because victimsfeel ashamed (taboo) to tell their problems, so victims think that if they leave the underworldof prostitution it will be difficult for them to get a job in real world life; Third, there issynergy between the community, government and law enforcement officials to jointlyeradicate the crime of prostitution in trafficking in persons, then the Police coordinate withthe Regional Police and Institutions outside the Police to find out the true identity of theperpetrators, and provide new job opportunities for those who want to leave the prostitutionprofession and start a decent life, as well as provide an understanding to the public so thatthey are willing to accept and give jobs to these former prostitutes.Keywords: Implementation, Prostitution in Person Trafficking, Crime